The Ability of Nutrition to Mitigate Epigenetic Drift: A Novel Look at Regulating Gene Expression. - D Palmer, Raymond; Papa, Veronica; Vaccarezza, Mauro (2021)
Epigenetic drift causes modification in gene expression during aging and a myriad of physiological changes that are mostly undesirable, remove youthful phenotype and are related to biological decay and disease onset. The epigenome is considered a stable regulator of genetic expression. Moreover, evidence is now accumulating that commonly available compounds found in foods can influence the epigenome to embrace a more youthful and therefore, more disease resistant state. Here we explore the correlation between nutriment and the epigenetic regulation through various types of alimentation. The aim is not to discuss specific chemicals involved in disease onset. Instead, we offer a brief glance at pathogens and offer a practical pathway into epigenetic regulation, hypothesizing that epigenetic drift might be attenuated by several foods able to drive a more youthful and disease resistant phenotype.